Assessing Mobile BRISMA LMS in Flipped Classroom Models to Improve Student Performance: A Structural Equation Modeling Approach - Mahdiyah, Mahdiyah; Haris, Haris; Wibawa, Basuki; Putri, Fildzah Rudyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
The integration of mobile technology in higher education has transformed traditional learning models into more flexible and student-centered approaches. However, challenges remain in effectively engaging students and improving learning outcomes. This study aims to examine the impact of Mobile BRISMA LMS on student academic performance within a Flipped Classroom model. A quantitative research design was employed using Structural Equation Modelling (SEM) to analyze the relationships among LMS usage, student engagement, teaching effectiveness, and academic achievement. The study involved 120 graduate students from Universitas Negeri Jakarta, selected through purposive sampling based on their enrollment in a flipped classroom course. The Mobile BRISMA LMS facilitated pre-class learning via video tutorials, interactive quizzes, and discussion forums, while in-class sessions emphasized collaboration and application of knowledge. The findings indicate that Mobile BRISMA LMS significantly enhances student engagement, which mediates the relationship between LMS usage and academic performance. Teaching effectiveness also plays a critical role in influencing student outcomes. In conclusion, Mobile BRISMA LMS effectively supports the Flipped Classroom model by fostering active learning, critical thinking, and improved academic achievement. These results offer practical insights for educators and institutions aiming to implement mobile LMS platforms to enhance learning experiences in higher education.